Health Risks of Indoor Exposure to Fine Particulate Matter and Practical Mitigation Solutions - National Academy of Engineering; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Schools, workplaces, businesses, and even homes are places where someone could be subjected to particulate matter (PM) – a mixture of solid particles and liquid droplets found in the air. PM is a ubiquitous pollutant comprising a complex and ever-changing combination of chemicals, dust, and biologic materials such as allergens. Of special concern is fine particulate matter (PM2.5), PM with a diameter of 2.5 microns (<0.0001 inch) or smaller. Fine PM is small enough to penetrate deep into the respiratory system, and the smallest fraction of it, ultrafine particles (UFPs), or particles with diameters less than 0.1 micron, can exert neurotoxic effects on the brain. Overwhelming evidence exists that exposure to PM2.5 of outdoor origin is associated with a range of adverse health effects, including cardiovascular, pulmonary, neurological and psychiatric, and endocrine disorders as well as poor birth outcomes, with the burden of these effects falling more heavily on underserved and marginalized communities. Health Risks of Indoor Exposure to Fine Particulate Matter and Practical Mitigation Solutions explores the state-of the-science on the health risks of exposure to fine particulate matter indoors along with engineering solutions and interventions to reduce risks of exposure to it, including practical mitigation strategies. This report offers recommendations to reduce population exposure to PM2.5, to reduce health impacts on susceptible populations including the elderly, young children, and those with pre-existing conditions, and to address important knowledge gaps.
Keywords: Health and Medicine; Engineering and Technology

Imagining the Future of Undergraduate STEM Education: Proceedings of a Virtual Symposium - National Academy of Engineering; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
In November 2020, the National Academies of Sciences, Engineering, and Medicine convened a multi-day virtual symposium on imaging the future of undergraduate STEM education. Speakers and participants pondered the future and the past and shared their goals, priorities, and dreams for improving undergraduate STEM education. Expert speakers presented information about today's students and approaches to undergraduate STEM education, as well as the history of transformation in higher education. Thoughtful discussions explored ideas for the future, how student-centered learning experiences could be created, and what issues to consider to facilitate a successful transformation. This publication summarizes the presentation and discussion of the symposium.
Keywords: Education

Promising Practices and Innovative Programs in the Responsible Conduct of Research: Proceedings of a Workshop - National Academy of Engineering; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The responsible conduct of research (RCR) is foundational to good science and engineering. However, there are several serious detrimental effects of research not conducted ethically and responsibly. Thus, federal legislation mandates that all National Science Foundation (NSF) grant recipients provide adequate training for undergraduate students, graduate students, and postdoctoral researchers about the Responsible Conduct of Research, and the National Institutes of Health (NIH) further specifies that topics such as conflict of interest, mentor/mentee responsibilities and relationships, collaborative research, and safe laboratory practices should be included in all instruction in RCR. To identify and disseminate information about exemplary RCR education practices and programs, the National Academy of Engineering convened a virtual workshop series October 6, 7, 20, and 21, 2021. This workshop provided a forum for interdisciplinary discussions of effective strategies for building an RCR culture in institutions along with potential improvements and further research in the area. It also highlighted selected exemplar RCR programs for administrators and faculty who are charged with RCR education and compliance at the institutional level. This publication summarizes the presentation and discussion of the workshop.
Keywords: Policy for Science and Technology

Frontiers of Engineering: Reports on Leading-Edge Engineering from the 2017 Symposium - National Academy of Engineering (The National Academies Press, 2018)
This volume presents papers on the topics covered at the National Academy of Engineering's 2017 US Frontiers of Engineering Symposium. Every year the symposium brings together 100 outstanding young leaders in engineering to share their cutting-edge research and innovations in selected areas. The 2017 symposium was held September 25-27 at the United Technologies Research Center in East Hartford, Connecticut. The intent of this book is to convey the excitement of this unique meeting and to highlight innovative developments in engineering research and technical work.
Keywords: Engineering and Technology

A New Vision for Center-Based Engineering Research - National Academy of Engineering; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The future security, economic growth, and competitiveness of the United States depend on its capacity to innovate. Major sources of innovative capacity are the new knowledge and trained students generated by U.S. research universities. However, many of the complex technical and societal problems the United States faces cannot be addressed by the traditional model of individual university research groups headed by a single principal investigator. Instead, they can only be solved if researchers from multiple institutions and with diverse expertise combine their efforts. The National Science Foundation (NSF), among other federal agencies, began to explore the potential of such center-scale research programs in the 1970s and 1980s; in many ways, the NSF Engineering Research Center (ERC) program is its flagship program in this regard.
Keywords: Engineering and Technology

Engineering a Learning Healthcare System: A Look at the Future: Workshop Summary - Institute of Medicine; National Academy of Engineering (The National Academies Press, 2011)
Improving our nation's healthcare system is a challenge which, because of its scale and complexity, requires a creative approach and input from many different fields of expertise. Lessons from engineering have the potential to improve both the efficiency and quality of healthcare delivery. The fundamental notion of a high-performing healthcare system—one that increasingly is more effective, more efficient, safer, and higher quality—is rooted in continuous improvement principles that medicine shares with engineering. As part of its Learning Health System series of workshops, the Institute of Medicine's Roundtable on Value and Science-Driven Health Care and the National Academy of Engineering, hosted a workshop on lessons from systems and operations engineering that could be applied to health care.
Keywords: Health and Medicine

Microbiomes of the Built Environment: A Research Agenda for Indoor Microbiology, Human Health, and Buildings - National Academy of Engineering; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
People's desire to understand the environments in which they live is a natural one. People spend most of their time in spaces and structures designed, built, and managed by humans, and it is estimated that people in developed countries now spend 90 percent of their lives indoors. As people move from homes to workplaces, traveling in cars and on transit systems, microorganisms are continually with and around them. The human-associated microbes that are shed, along with the human behaviors that affect their transport and removal, make significant contributions to the diversity of the indoor microbiome.
Keywords: Biology and Life Sciences; Engineering and Technology